Absorbable antibiotic beads as an adjuvant therapy in treating ventricular assist devices driveline infection: A case report. Issue 8 (11th July 2020) - Haddad, Osama; Pham, Anthony N.; Thomas, Mathew; Ali, Mojahid; Sareyyupoglu, Basar; El‐Sayed Ahmed, Magdy M.; Pham, Si M.
Abstract: Background: Ventricular assist devices driveline infections are common, recalcitrant, and carry high morbidity and mortality. Herein, we reported a patient with driveline infection that was successfully treated with a combination of systemic antibiotics, surgical debridement, and instillation of absorbable antibiotic beads to the wound bed. Methods and Results: A 39‐year‐old man with nonischemic cardiomyopathy underwent insertion of a continuous flow left ventricular assist device. Four years postoperatively, the patient presented with clinical, laboratory, and radiologic signs of driveline tract infection. He underwent extensive surgical debridement, installation of absorbable antibiotic beads that consisted of calcium sulfate, vancomycin, and tobramycin, into the wound bed, and systemic antibiotics. The patient was free of infection 9 month postoperatively. Conclusion: Absorbable calcium sulfate antibiotic beads may serve as a beneficial adjunct to surgical debridement and systemic antibiotics for the treatment of ventricular assist device driveline infection, and merit further investigation.